Don't drop the mic : the power of your words can change the world - Jakes, T. D.; Thomas, Frank A. (Frank Anthony), 1955- (Faith Words, 2021)
"In Don't Drop the Mic, Bishop Jakes speaks to readers about communication and how the ways we speak and interact with others can be part of our everyday ministries. He helps readers understand: Why the way we speak and the words we use matter How speaking well, no matter your topic or audience, improves your chances of getting the result you want How to craft your message, whether it's a simple email or a speech under the spotlights, to connect with listeners Why good communication is important for building connection and community How sharing God's Word produces abundant fruit Drawing lessons from Scripture and his own life, Jakes gives career advice for those who have or want to grow into a speaking career, but he also provides clear direction and insight for everyone who gives presentations, writes emails, or talks to other people in their job or home life. There will be practical advice about how to craft insightful and meaningful communications, but the heart of this book is really about how we can communicate more clearly to build community and share the hope of Christ in our everyday lives. The more adept we become at using all available resources to convey our message, the greater our impact. From lovers to litigators, entrepreneurs to entertainers, and bloggers to board members, we all want to communicate more effectively, intimately, and efficiently. Whether you're interviewing for a new position, proposing a new business plan, auditioning for a performance, delivering a report for your committee, teaching Sunday school, or sharing your heart with a loved one, this book will help"--